Housekeeping Practices Towards Customer Satisfaction in the Bellevue Hotel at Timog, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the housekeeping practices that affect customersatisfaction in the Bellevue Hotel in Timog Quezon City.The results of this study reveal that the hotel is doing a great job in providing guest satisfactionto the customers where the respondents described the housekeeping practices of the hotel interms of cleanliness of the guest rooms, efficiency of the services offered, and wastemanagement as strongly satisfying.Customer satisfaction in terms of room ambiance, security services, and facilities wasassessed as highly observed. This study recommends that the hotel maintain the quality of theprocesses that ranked with the highest satisfaction and observation except for the two: speedof delivery of loaned items and waste disposal, where the study found that customers had thelowest satisfaction level.
Keywords: Hospitality Management